PENGARUH KESADARAN WAJIB PAJAK DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MELAPORKAN SURAT PEMBERITAHUAN TAHUNAN (SPT) DITENGAH PANDEMI COVID-19 DENGAN SANKSI PAJAK SEBAGAI VARIABEL MODERATOR - Suratminingsih; Lisdawati; Tagor Maulana Daulay (RELEVAN : Jurnal Riset Akuntansi, 2021)
This study aims to determine the effect of taxpayer awareness and tax knowledge on taxpayer compliance inreporting Annual Tax Returns (SPT) in the midst of the Covid-19 pandemic with tax sanctions as moderating variables for individual taxpayers registered at KPP Pratama Pondok Gede. The research method used is a quantitative method. Data collection techniques were carried out using primary and secondary data types. The primary data was obtained from questionnaires distributed to 100 respondents and the secondary data was obtained from statistical data on annual SPT reporting at KPP Pratama Pondok Gede. Sampling using incidental sampling technique. The hypothesis test used is multiple linear regression analysis and moderated regression analysis with the interaction method. The results showed that Taxpayer Awareness had a positive effect on Taxpayer Compliance in the midst of the Covid-19 pandemic on individual taxpayers registered at KPP Pratama Pondok Gede. This study also shows that tax sanctions as a moderator are not able to moderate the effect of Taxpayer Awareness and Tax Knowledge in Taxpayer Compliance amid the Covid-19 Pandemic in individual taxpayers registered at KPP Pratama Pondok Gede.